Pharmacy and Nursing Students' Knowledge and Practices Concerning the Disposal of Unused and Expired Medicines in Kosovo - Selvete Shuleta-Qehaja; Nita Kelmendi (MDPI AG, 2022)
This descriptive cross-sectional study aimed to assess the knowledge and practices of pharmacy and nursing students at a medical college in Kosovo concerning unused and expired medications. A self-administered questionnaire was distributed to 500 randomly selected students of pharmacy (200 questionnaires) and nursing students (300 questionnaires). Overall, 336 returned the filled forms and the response rate was 67.2. SPSS version 26.0 was utilized for statistical analysis. The results showed that 89.2% of pharmacy students and 82.2% of nursing students check the expiration date of medications before purchasing them and a considerable number of students stated that they possess unused medicines at home (78.4% of pharmacy and 74% of nursing students). Regarding disposal practice, over 50% of both nursing and pharmacy students dispose of unused and expired medications in the trash. A small proportion of students returned unused or expired medicines to the pharmacy (11.4% of pharmacy students and 10.7% of nursing students return unused medications, whereas 14.4% of pharmacy respondents and 10.1% of nursing respondents reported returning expired medicines). There was a statistically significant difference in the ways pharmacy and nursing students purchase pharmaceuticals and in their opinions regarding institutions in charge of disposing of unused and expired medicines (p = 0.000). Students are aware of the detrimental effects improper disposal of unused and expired medicines has on the environment and public health, but lack information regarding the return of unused and expired medicines to the pharmacy. To change the existing practice the most appropriate method would be to add additional lectures on safe disposal practices into existing modules. It is recommended for involved stakeholders in Kosovo to organize training, seminars, and workshops for health professionals especially pharmacists and nurses, since they pass the information to patients/consumers as well as the government to make amendments to current legislation to ameliorate the returning procedures for patients/consumers in pharmacies.